Model Integratif Pendidikan Karakter Berbasis Nilai-Nilai Qur’ani dalam Penguatan Moral dan Spiritualitas Pendidikan Islam - Aimatul Khoiriyah; Miftahul Jannah; Hera Hapsari Kusuma; Miasari; Ahsan Hakim (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
This study aims to analyze the philosophical foundations of Qur’anic-based character education and to develop an integrative character education model as a response to moral degradation and value disorientation in modern society. Employing a qualitative approach with a library research method, the study draws on primary sources consisting of the Qur’an, Hadith, and classical as well as contemporary tafsir, complemented by secondary data from relevant books and peer-reviewed journal articles published between 2016 and 2025. Data were analyzed using content analysis through data reduction, data display, and conclusion drawing, strengthened by source triangulation and comparative analysis. The findings reveal that Qur’anic character education is firmly grounded in the Islamic anthropological view of humans as khalīfah fī al-arḍ, endowed with fitrah that must be developed through tazkiyatun nafs and ta’dīb to achieve the ideal of insān kāmil. Core Qur’anic values tauhid, akhlaq, ‘amal ṣāliḥ, ‘adl, and raḥmah form an integral moral system that harmonizes spiritual and social dimensions. This study proposes the Integrative Qur’anic Character Education Model (MPKQI), comprising divine internalization, social transmission, and personal transformation, which extends conventional character education theories by incorporating a transcendental, revelation-based dimension. The study concludes that Qur’anic-based character education offers both theoretical and practical contributions to global moral and spiritual education in addressing contemporary ethical challenges.